Effect of Curcumin on Aspergillus parasiticus Growth and Expression of Major Genes Involved in the Early and Late Stages of Aflatoxin Biosynthesis - Z Jahanshiri; M Shams-Ghahfarokhi; A Allameh; M Razzaghi-Abyaneh (Tehran University of Medical Sciences, 2012)
Background: The effect of curcumin as a natural safe compound with different biological activities was examined on fungal growth and aflatoxin production in Aspergillus parasiticus NRRL 2999. Methods: The fungus was cultured in presence of serial two-fold concentrations of curcumin (125-2000 µg/ml) in yeast extract sucrose broth for 3 days at 28°C. Mycelia dry weight was determined as an index of fungal growth, while aflatoxin production was assessed by high performance liquid chromatography (HPLC). The expression of ver-1, nor-1, pksA, omtA and aflR genes in aflatoxin biosynthetic pathway was evaluated by real time PCR. Results: Curcumin strongly inhibited aflatoxin B1 production in the range of 26.6 to 94.9% by serial two-fold concentrations from 125 to 2000 µg/ml. Fungal growth was also inhibited by the compound in the range of 34.0 to 60.8%. Analysis of the expression of aflatoxin pathway genes by real time PCR showed that curcumin inhibited the expression of ver-1, nor-1, pksA, omtA and aflR genes at concentrations of 250 and 1000 µg/ml. In concentration of 1000 µg/ml, gene expression was reduced by 31.3%, 44.6%, 57.1% 110.9% and 286.7% accordingly. Reduction in the expression of aflatoxin biosynthesis genes was significant only for aflR. In ferric reducing ability of plasma (FRAP) assay, curcumin showed strong antioxidant activity at all concentrations tested. Conclusion: Curcumin may be employed successfully as a good candidate in controlling of toxigenic fungal growth on food and feed and subsequent contamination with aflatoxins in practice.